Representasi Kode IRMA pada Basis Data Mammografi MIAS - Karmilasari Karmilasari; Suryarini Widodo; Lussiana ETP (UIN Sultan Syarif Kasim Riau, 2012)
Limitations of mammography database with image coding and the identification of a variety ofcharacteristics, such as pathology, and abnormal breast tissue types, is an issue in the development ofcomputer systems for the diagnosis of breast cancer. IRMA coding system was developed to facilitatecontent-based image retrieval identify (CBIR) as a prototype application in medical diagnostic radiologyimagery. IRMA Code was developed following the network code American College of Radiology (ACR)and data system (BI-RAD). Through IRMA code, obtained standardized code for the type of tissue, thelevel of tumor and lesion description. The results of the code in the form of a character string of no morethan 13 characters (IRMA: YYYY - DDD - AAA - BBB). The code can be extended by introducingcharacters in certain positions code if there is a new modality is introduced. IRMA coding system can beapplied to mammographic Digital Mammogram Image Analysis Society (MIAS). Complete initialinformation from mammography is the basis for the study of medical image breast cancer, while the finalinformation obtained from IRMA coding system can be input for clinicians in decision-making for patientaction.Keywords : Mammography, IRMA coding system, MIAS database